TINJAUAN YURIDIS TERHADAP TINDAK PIDANA EKONOMI PUPUK BERSUBSIDI - Sarmadan Pohan (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Subsidized Fertilizer is goods under supervision whose procurement and distribution is subsidized by the government for the needs of Farmer groups and / or Farmers in the agricultural sector including Urea fertilizer, SP 36 Fertilizer, ZA Fertilizer, NPK Fertilizer, and other types of subsidized fertilizers as determined by Government affairs in agriculture. This objective is to see how the legal arrangements regarding the supervision, procurement and distribution of Subsidized Fertilizer and to see how the judge's consideration in imposing sanctions on the economic crime of Subsidized Fertilizer at the Padangsidimpuan District Court. Economic Crime is a criminal act in Articles 1e, 2e and 3e of the Emergency Law Number 7 of 1955 concerning Investigation, Prosecution and Economic Justice. One of the criminal acts in economic crime is the trading of goods under the supervision of Subsidized Fertilizer, this is in accordance with the Regulation of the President of the Republic of Indonesia Number 15 of 2011 concerning Stipulation of Subsidized Fertilizer as goods under Supervision. In the juridical analysis, the Panel of Judges is in accordance with the elements in the facts at the trial